Optimization of Spray Parameters and Corrosion Properties of Plasma-Sprayed Cr2O3 Coatings Using Response Surface Methodology - Minghui Liu; Zhiwen Tan; Yuantao Zhao; Haoran Wang; Shitao Zhang; Rong Ma; Tao Jiang; Zhen Ma; Ning Zhong; Wenge Li (Crystals)
In this study, the experimental design of response surface methodology was used to explore the interaction between spraying parameters to obtain an optimized process to reduce the porosity of the coating, and to prepare an excellent chromium oxide coating. The order of the single parameter affecting porosity is as follows: power > main gas > spraying distance > carrier gas flow. This study found that the spraying process with the lowest porosity of the chromium oxide coating is as follows: power of 625 W, stand-off distance of 105 mm, primary gas of 42.5 lpm, carrier gas flow of 5 lpm, and feed powder delivery rate of 35 g/min. The EDS results show that the Cr and O elements in the coating with the lowest porosity are uniformly distributed, while for the coating with the highest porosity, the elements are unevenly distributed to a certain extent, which is caused by the unevenness of the structure caused by the structure defects. The corrosion current density of chromium oxide coating VI (low porosity) is 4.34 × 10⁻⁶ A, whereas that of chromium oxide coating IV (high porosity) is 1.862 × 10⁻⁵ A. On the coating with the highest porosity, the corrosion activity is dominant, while the minimum porosity of coating is the smallest.